Diversidade e evolução na simbiose entre bactérias e formigas Attini - Marchiori, Ana Carolina [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Ants of the Attini tribe are known for the habit of cultivating mutualistic fungi (Basidiomycota) on a variety of harvested materials to form what is called the fungus garden. This habit originated approximately 50 million years ago in South America and gave rise to five agricultural systems, which differ in the type of fungus and collected material. Attine ants utilize the fungus garden as a source of nutrients and enzymes, which are not only produced by the mutualistic fungus, but also by other microbes present in the garden. Therefore, for ants and fungi have access to these nutrients associations with other microorganisms became necessary. Studies of microbial community associated with attine ants are mostly related to the fungus gardens and aim to explore the mechanisms of plant biomass degradation. Information on the microbiota associated with the body of ants and its function are still lacking. Attine ants rely on microbial symbionts for nutrition and protection against parasites. On the other hand, some microbes threatens these ants and others appear to be only commensals. In this work, the bacteria associated with the attine ants Atta laevigata, Trachymyrmex urichi and Mycocepurus goeldii were identified by culture-independent methods and a scenario in which the evolution of attine ants is shaped by the interaction with these microorganisms has been proposed. In the present study a washing protocol was also developed to remove external bacteria, and used to sample microorganisms living inside the ants and possibly other insects. The results showed differences between the bacterial communities harbored by the attine ants studied. Discrimination of internal and external ants’ body bacteria was possible due to the standardization and application of the developed washing protocol. It was observed that the intestines of most basal attine M. goeldii are dominated by a single species of Spiroplasma. However, during the attine ants’ evolution, this bacterium was progressively replaced by two Rhizobiales species in the gut of the phylogenetically intermediate T. urichi, and finally a single species of Rhizobiales prevailed as the unique bacterial species in the gut of the most derived leaf-cutter ant A. laevigata. Leaf-cutters also harbor on their cuticles considerable amounts of Acetobacter sp. Both Rhizobiales and Acetobactersp. species are in the group of nitrogen-fixing bacteria. Thus, it is conceivable that specialization in nitrogen-fixing mutualists may have played a role in increasing population and body size during Attini evolution. A larger population is thought to be associated with increases in infection rates, but this tendency was apparently counterbalanced by high social complexity of leaf-cutters and by the maintenance of Burkholderiales and Actinomycetales species, which we only found in the cuticle of ants. These antibiotic-producing bacteria may have assumed the protective role that is currently attributed to Pseudonocardiaceae in the remaining Attini species. We also detected an association with cuticular Wolbachia mutualists, which may have begun in the more primitive Attini, then specialized in the intermediate ones, and finally being lost in the more derived leaf-cutters. Mutualistic associations appear to be recent and originated from a single acquisition of nitrogen-fixing bacteria and multiple acquisitions of antibiotic producing microbes.

As formigas da tribo Attini são conhecidas pelo hábito de cultivar fungos mutualistas (Basidiomycota) em uma variedade de materiais coletados para formar o que é chamado de jardim de fungo. Este hábito teve início há cerca de 50 milhões de anos na América do Sul e deu origem a cinco tipos de agricultura, que diferem no tipo de fungo e material coletado. As attíneas utilizam os jardins de fungos como fonte de nutrientes e enzimas, os quais são produzidos não somente pelo fungo mutualista, mas também por outros microrganismos presentes no ninho. Portanto, para as formigas e fungos terem acesso a nutrientes são necessárias associações com outros microrganismos. Estudos das comunidades microbianas associadas às formigas Attini, na maioria das vezes, estão relacionados aos jardins de fungo e objetivam explorar os mecanismos de degradação da biomassa vegetal. Informações sobre a microbiota associada ao corpo das formigas e sua função ainda são insuficientes. As attíneas dependem dos simbiontes para sua nutrição e proteção contra parasitas. Mas alguns desses microrganismos são ameaças às formigas e outros parecem ser apenas comensais. No presente trabalho, as bactérias associadas às formigas Attini Atta laevigata, Trachymyrmex urichi eMycocepurus goeldii foram identificadas por métodos independentes de cultivo e um cenário no qual a evolução das formigas Attini é moldada pela interação com estes microrganismos foi proposto. Além disso, foi desenvolvido um protocolo de lavagem das formigas para eliminar bactérias externas e ser utilizado para amostrar os microrganismos do interior das formigas. Os resultados mostraram diferenças entre as comunidades bacterianas abrigadas pelas formigas Attini estudadas. A discriminação de bactérias internas e externas ao corpo das formigas foi possível devido à padronização e aplicação do protocolo de lavagem desenvolvido. Foi descoberto que nos intestinos da Attini mais basal M. goeldii predomina uma única espécie de Spiroplasma. No entanto, durante a evolução, esta bactéria foi progressivamente substituída por duas espécies de Rhizobiales no intestino da attínea filogeneticamente intermediária T. urichi, e finalmente uma única espécie de Rhizobiales prevaleceu como a espécie bacteriana única nos intestinos da formiga cortadeira mais derivada A. laevigata. As cortadeiras também carregam em suas cutículas, quantidades consideráveis de Acetobacter. Rhizobiales e Acetobacter pertencem a grupos de bactérias fixadoras de nitrogênio. Assim, é concebível que a especialização em mutualistas fixadores de nitrogênio possa ter desempenhado um papel no aumento do tamanho da população e do tamanho do corpo ao longo da evolução das formigas Attini. O aumento da população pode estar associado com o aumento nas taxas de infecção, mas esta tendência foi aparentemente compensada pela alta complexidade social das cortadeiras e pela manutenção de espécies de Burkholderiales e Actinomycetales, encontradas na sua cutícula. Estas bactérias produtoras de antibióticos podem ter assumido o papel protetor que está atribuído a Pseudonocardiaceae nas demais espécies de Attini. Também foi detectada uma associação com espécies de Wolbachia que parecem ser mutualistas e externas ao corpo das attíneas, provavelmente nas cutículas. Esta associação pode ter iniciado na Attini mais basal, se especializado na intermediária, mas foi perdida na mais derivada. As associações mutualistas parecem ser recentes e ter se originado a partir de uma única aquisição das fixadoras de nitrogênio e múltiplas aquisições de bactérias que produzem antibióticos.
Keywords: Ants; Formiga; Simbiose; Microbiota; Formigas - Nutrição; Bacterias; Formiga-cortadeira; Nitrogenio - Fixação